2017
DOI: 10.1016/s1569-9056(17)30701-7
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of papillary versus clear cell renal cell carcinoma varies significantly in non-metastatic disease

Abstract: Renal cell carcinoma (RCC) comprises a heterogenous group of tumors. Traditionally, papillary RCC (pRCC) is associated with a favorable outcome compared to clear cell RCC (ccRCC), while other series report equivalent or worse prognosis. In this paper we comparatively evaluate outcome of pRCC versus ccRCC in two large multi-institutional databases (cohort study), including distribution of pRCC subtypes 1 and 2. Retrospective data of 1,943 surgically treated pRCC patients from 17 European/ North American centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…For example, some studies concluded that the prognosis of localized pRCC was more favorable than that of ccRCC, while the prognosis of advanced/metastatic pRCC was worse than that of ccRCC 6‐8 . However, conflicting results were observed in other studies, in which metastatic pRCC and metastatic ccRCC had similar prognoses 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies concluded that the prognosis of localized pRCC was more favorable than that of ccRCC, while the prognosis of advanced/metastatic pRCC was worse than that of ccRCC 6‐8 . However, conflicting results were observed in other studies, in which metastatic pRCC and metastatic ccRCC had similar prognoses 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…The notion that different histologic subtypes harbor varying biologic capacities has long been appreciated and has different implications in the early-stage and advanced setting. Indeed, large cohort studies of patients with nonmetastatic papillary RCC (PRCC) demonstrate favorable outcomes compared to ccRCC patients, while PRCC patients fared worse than their ccRCC counterparts in the metastatic setting (6,7).…”
mentioning
confidence: 99%